BUSINESS DEVELOPMENT STRATEGY OF PESANTREN'S COOPERATIVES: LESSONS FROM PESANTREN DAARUT TAUHIID - Irfany, Mohammad Iqbal; Rahmat, Muhammad Alifka; Haq, Daffa Aqomal (Universitas Airlangga, 2024)
Introduction: Islamic boarding schools have significant potential to boost the Sharia economy, notably through cooperative formation. However, many of these cooperatives, including the Daarut Tauhiid Islamic Boarding School Cooperative (DT Cooperative), are not performing optimally. DT Cooperative contributes only 5% to the school's financial independence, and its residual business result (sisa hasil usaha, SHU) has varied over the last three years. This research aims to identify DT Cooperative's strengths, weaknesses, opportunities, and threats, and to establish strategic priorities for cooperative development. Methods: The Analytical Network Process (ANP) with a Strength-Weakness-Opportunity-Threat (SWOT) network was employed in this study. Results: The findings of this study indicate that strength is the top priority in establishing the DT Cooperative business. The most influential characteristics of strengths, weaknesses, opportunities, and dangers are a structured organization, suboptimal marketing management, a huge market share, and shifting company dynamics. The most important approach to pursue is to increase cooperation among various groups. Conclusion and suggestion: This research highlights the need to improve organizational relationships and address marketing management deficiencies in DT Cooperatives. By leveraging organizational strengths and fostering collaboration, Islamic boarding school cooperatives can better support Sharia economic efforts. Insights from this study apply to Daarut Tauhiid and similar cooperatives, and underscore the importance of policies that enhance training, consultation, and networking among Islamic boarding schools. This study contributes to the economic development knowledge of Islamic boarding schools, particularly cooperatives, in enhancing community welfare and supporting their economic independences.